2021
DOI: 10.1098/rspb.2020.2438
|View full text |Cite
|
Sign up to set email alerts
|

Investment in chemical signalling glands facilitates the evolution of sociality in lizards

Abstract: The evolution of sociality and traits that correlate with, or predict, sociality, have been the focus of considerable recent study. In order to reduce the social conflict that ultimately comes with group living, and foster social tolerance, individuals need reliable information about group members and potential rivals. Chemical signals are one such source of information and are widely used in many animal taxa, including lizards. Here, we take a phylogenetic comparative approach to test the hypothesis that soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 103 publications
(164 reference statements)
0
11
0
Order By: Relevance
“…Femoral glands are usually dimorphic and, in general, more developed in males than in females [ 10 , 12 , 13 ]. Recent comparative analyses suggested that FGs and other epidermal glands may have played a role in the evolution of sociality in this vertebrate group [ 14 ]. Indeed, it is well known that FG secretions are involved in many social interactions (reviewed in [ 12 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Femoral glands are usually dimorphic and, in general, more developed in males than in females [ 10 , 12 , 13 ]. Recent comparative analyses suggested that FGs and other epidermal glands may have played a role in the evolution of sociality in this vertebrate group [ 14 ]. Indeed, it is well known that FG secretions are involved in many social interactions (reviewed in [ 12 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in lizards the basic morphological hardware to produce olfactory signals, i.e. the number of chemical signalling glands, correlated with social grouping [23], suggesting that this rather rough proxy of communicative complexity is sufficient to invoke convergent coevolution with social complexity.…”
Section: Discussionmentioning
confidence: 99%
“…In birds, cooperative breeders exhibit larger vocal repertoires [19,20], experimental manipulations of group size caused changes in song complexity [21] and group-living facilitated duetting [22]. In lizards, social grouping covaries positively with the number of chemical signalling glands [23], whereas the visual display repertoire size is inversely associated with home range size [24]. Finally, in insects, sensory systems and chemical signals coevolved with group-living in halictid bees [25].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple factors unrelated with alternative communication channels have been shown to influence epidermal glands and chemical signals in reptiles. For instance, sociality in lizards is associated with the presence of femoral glands indicating an important role of chemosignaling on squamate social grouping 78 . In addition, the composition of chemical signals produced by femoral glands is shaped by diet 79 81 , climate conditions 25 , 82 and predation pressure 83 .…”
Section: Discussionmentioning
confidence: 99%